2016
DOI: 10.7448/ias.19.1.21096
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and predictors of estimated HIV transmissions and bacterial STI acquisition among HIV‐positive patients in HIV care across three continents

Abstract: IntroductionSuccessful global treatment as prevention (TasP) requires identifying HIV-positive individuals at high risk for transmitting HIV, and having impact via potential infections averted. This study estimated the frequency and predictors of numbers of HIV transmissions and bacterial sexually transmitted infection (STI) acquisition among sexually active HIV-positive individuals in care from three representative global settings.MethodsHIV-positive individuals (n=749), including heterosexual men, heterosexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…Specifically, in Brazil and in a combined-country model, the highest frequencies of religious service attendance (compared to never/rarely attending) were associated with lower likelihood of ART adherence as alcohol problems increased. Substance use, including problematic alcohol use, was related to lower ART adherence (63,64) and higher STI incidence and HIV transmission risk in the HPTN 063 cohort (43). In one independent sample of persons in HIV outpatient care in Rio Grande, Brazil, the prevalence of unhealthy alcohol use prevalence among people living with HIV was 29% (65).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Specifically, in Brazil and in a combined-country model, the highest frequencies of religious service attendance (compared to never/rarely attending) were associated with lower likelihood of ART adherence as alcohol problems increased. Substance use, including problematic alcohol use, was related to lower ART adherence (63,64) and higher STI incidence and HIV transmission risk in the HPTN 063 cohort (43). In one independent sample of persons in HIV outpatient care in Rio Grande, Brazil, the prevalence of unhealthy alcohol use prevalence among people living with HIV was 29% (65).…”
Section: Discussionmentioning
confidence: 96%
“…HPTN 063 was an observational, longitudinal year-long, multisite cohort study of HIVinfected individuals in care in Brazil (Rio De Janeiro), Thailand (Chiang Mai), and Zambia (Lusaka) (43). HPTN 063 was designed as a preparedness study to acquire data to develop interventions to decrease sexual transmission by people living with HIV, and to determine whether the same interventions could be effectively deployed in patients from multiple risk groups and cultural settings.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the pooled IR (6.63/100 person-year, p < 0.05)) in our meta-analysis was within the range of the incidence rate of HIV (1.2 to 14.4/100 person-year) in MSM population reported by WHO 24 . The overall weighted IR was highly influenced by the number contributed from Brazil 25 . This extreme data indicated that the risk of HIV transmission among MSM may be different within distinct regions.…”
Section: Discussionmentioning
confidence: 99%